Feminisms in development : contradictions, contestations and challenges - Cornwall, Andrea, 1963-; Harrison, Elizabeth, 1963-; Whitehead, Ann, 1946- (Zed Books ; Distributed in the USA exclusively by Palgrave Macmillan, 2007)
This collection of essays by leading feminist thinkers from North and South constitutes a major new attempt to reposition feminism within development studies. Feminism?s emphasis on social transformation makes it fundamental to development studies. Yet the relationship between the two disciplines has frequently been a troubled one. At present, the way in which many development institutions function often undermines feminist intent through bureaucratic structures and unequal power quotients. Moreover, the seeming intractability of inequalities and injustice in developing countries have presente.